A Teoria da subjetividade e o ensino de ciências: Estado da Arte e desafios para criação de uma ambiência favorável ao processo ensino-aprendizagem - Guedes Martinez, Isabella; Tambara Marzola, Maria Eduarda; Batista dos Santos, Elias (Saberes: Revista interdisciplinar de Filosofia e Educação, 2023)
This abstract is characterized as a research about a State of the Art whose purpose was to map the works focused on the theme of the student who emerges as a subject in his teaching-learning process. In this sense, we also aimed to contribute to the understanding of the importance of the school environment being considered and assumed as a locus that favors the production and expression of subjective meanings that constitute the teaching-learning process. For these purposes, research was carried out that subsidized us with regard to access to works in the area. The corpus of analysis considered in this research were the publications of 2011 and 2022, found among the works of the National Meeting of Encontro Nacional de Ensino, Pesquisa e Extensão (ENEPe), in the repository of the State Universidade Estadual de Goiás (UEG), in the repository of the Universidade de Brasília (UnB), and in the Google Scholar database. From our research, it was possible to organize the themes into categories: Subject and human relations in the classroom, Subject and creativity in learning, Social subjectivity and creativity in learning, Subject who learns, Subjective senses, Subjectivity and history of life, subjectivity and teaching through research. As a theoretical, methodological and epistemological basis, we use the guiding principles of Qualitative Epistemology, presiding over the cultural-historical perspective of subjectivity developed by González Rey. Regarding the conclusion, we could perceive ways that favored a favorable environment for the subject who learns and need for the production of more studies in this sense.